The genus Heteromphrale Kröber, 1937 (Diptera; Scenopinidae) in Peru, with the description of a new species - Sánchez , Pável (2023)
The Neotropical genus Heteromphrale Kröber, 1937, so far known from Argentina, Chile and Uruguay, is recorded for the first time from Peru based on the description of a new species, Heteromphrale illapa sp. nov. from Moquegua. An update to the key to the known species is provided, as well as a distribution map. Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:2381F844-1F44-4AEE-8032-5F6D4199333CActo nomenclatural/nomenclatural act:Heteromphrale illapa Sánchez & Ramírez-Montano, 2023LSIDurn:lsid:zoobank.org:act:546EC70C-0FAA-403F-89A0-4D673E5BF0E4